Mechanisms Involving Sensory Pathway Steps Inform Impacts of Global Climate Change on Ecological Processes - Rivest, Emily B.; Jellison, Brittany; Ng, Gabriel; Satterthwaite, Erin V.; Bradley, Hannah L.; Williams, Susan L.; Gaylord, Brian (Frontiers in Marine Science, 2019)
Human-caused environmental change will have significant non-lethal and indirect impacts on organisms due to altered sensory pathways, with consequences for ecological interactions. While a growing body of work addresses how global ocean change can impair the way organisms obtain and use information to direct their behavior, these efforts have typically focused on one step of the pathway (e.g. reception of a cue/signal), one sensory modality (e.g. visual), or one environmental factor (e.g. temperature). An integrated view of how aspects of environmental change will impact multiple sensory pathways and consequently ecological processes is needed to better anticipate broader consequences for marine ecosystems. Here, we present a conceptual synthesis of effects of global change on marine sensory ecology, based on a literature review. Our review supports several predictions for how particular sensory pathway steps – production, transmission, and reception/processing of cues/signals - are affected by environmental change. First, the production and reception/processing of multiple modalities of cues/signals are vulnerable to multiple global change stressors, indicating that there are generalizable mechanisms by which environmental change impairs these pathways steps, leading to altered sensory pathway outcomes. Factors that enhance organismal stress as a whole may amplify impacts to these sensory pathways. Second, global change factors tend to affect specific modalities of cue/signal transmission. Consequently, local impacts on ecological processes linked with cue/signal transmission will vary depending on environmental stressor(s) present and the corresponding sensory modality. Finally, because many ecological and evolutionary interactions rely on sensory processing, impairment of sensory pathways may frequently underpin impacts of global ocean change on marine ecosystems. Effects on individual sensory processes will integrate to shape processes like mating, predation, and habitat selection, and we highlight new insights on impacts to ecological interactions by employing our mechanistic conceptual framework.